Air travel choice, online meeting and passenger heterogeneity – An international study on travellers' preference during a pandemic. (November 2022) - Chen, Tiantian; Fu, Xiaowen; Hensher, David A.; Li, Zhi-Chun; Sze, N.N.
Abstract: This study empirically identifies business travellers' preferences during the COVID-19 pandemic across different regions. A stated preference study was conducted during April to June 2021 on respondents in the U.S., the city of Shanghai in mainland China and Hong Kong. Generalised mixed multinomial logit (GMXL) models are estimated incorporating attributes of travel characteristics, severity levels of the pandemic, and health control measures at the airport. When an online meeting is inapplicable, respondents from Shanghai and Hong Kong highly value heath control measures, and are not sensitive to the time spent at airport health checkpoints. In comparison, U.S. respondents are averse to the time spent for health check, the reporting of personal information, travel history, symptoms, and the requirements of compulsory mask wearing and onsite sample testing. However, when online meeting is applicable, all the respondents show no appreciation for health control measures, while the U.S. respondents are twice more averse to the time spent at airport health checkpoints. Online meeting reduces the intention of international business travel amid the pandemic for passengers in Shanghai and Hong Kong, but imposes no significant effects on U.S. travellers. Such significant heterogeneity in traveller preference partly explains the different recovery patterns observed in various aviation markets, and justifies individualized travel arrangements and service priority in fulfilling pandemic control requirements across different regions. Our study also suggests that there are commonly accepted areas for global cooperation such as the sharing of vaccination record, and the option of online meeting calls for convenient travel arrangements amid pandemic to all countries.